Creating a Conducive Policy Environment for a Food Secure SADC - Takavarasha, Tobias (FANRPAN, 2006)
This 2005 workshop was organized as part of FANRPAN mission and mandate to facilitate public policy research as well as multi-stakeholder dialogues at different levels.